Effects of Deep Brain Stimulation on Eye Movements and Vestibular Function - Shaikh, Aasef G.; Antoniades, Chrystalina; Fitzgerald, James; Ghasia, Fatema F. (Frontiers in Neurology, 2018)
Discovery of inter-latching circuits in the basal ganglia and invention of deep brain stimulation for their modulation is a breakthrough in basic and clinical neuroscience. The deep brain stimulation not only changes the quality of life of hundreds of thousands of people with intractable movement disorders, but it also offers a unique opportunity to understand how the basal ganglia interacts with other neural structures. An attractive yet less explored area is the study of deep brain stimulation on eye movements and vestibular function. From the clinical perspective such studies provide valuable guidance in efficient programming of stimulation profile leading to optimal motor outcome. From the scientific standpoint such studies offer the ability to assess the outcomes of basal ganglia stimulation on eye movement behavior in cognitive as well as in motor domains. Understanding the influence of deep brain stimulation on ocular motor function also leads to analogies to interpret its effects on complex appendicular and axial motor function. This review focuses on the influence of globus pallidus, subthalamic nucleus, and thalamus deep brain stimulation on ocular motor and vestibular functions. The anatomy and physiology of basal ganglia, pertinent to the principles of deep brain stimulation and ocular motility, is discussed. Interpretation of the effects of electrical stimulation of the basal ganglia in Parkinson’s disease requires understanding of baseline ocular motor function in the diseased brain. Therefore we have also discussed the baseline ocular motor deficits in these patients and how the deep brain stimulation changes such functions.